A Critique and Review on the Book Human Resource Management in Public Organizations - Mohammad Mohammadi; Fatemeh Lali (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The production of books and other scientific texts tailored to the requirements of public organizations is an inevitable necessity, due to the special characteristics of these organizations. The book "Human Resource Management in public Organizations" by Darvish (PhD) and Almasifard (PhD) is one of the texts that has been written to address this need. In the present article, this book has been criticized by the descriptive-analytical method. In this regard, first, the authors are introduced, then it is described based on the form and content, and last it is evaluated and analyzed in three dimensions of appearance, structure, and content. Despite having its own advantages and strengths, the evaluation shows that this book needs to be reviewed and corrected in the above three dimensions, especially the production of appropriate content to human resource management in the public sector.